Frontiers in Oral Mucosal Immunity and the Microbiome - Belibasakis, Georgios N.; Hajishengallis, George (Frontiers in Oral Health, 2022)
The 2nd International Conference on Oral Mucosal Immunity and the Microbiome (OMIM) took place at the Grecotel Kos Imperial Hotel, Kos, Greece, between 25th and 30th September 2021, under the auspices of the Aegean Conferences. This has only been the second Aegean Conference of this thematic, the first one having taken place in 2018 in Crete, during the same period of the year. Given the hardships in travel and heightened infection transmission risks amid the COVID-19 pandemic, the Conference was well attended by 29 international speakers across the world. For many of the participants, this was the first conference travel in the post-pandemic era, and quite significant that it has taken place on the island of Hippocrates. Stringent regional health and safety regulations had to be followed to accomplish for this in-person Conference to take place. Frontiers in Oral Health has hosted papers from presentations of the Conference, whereas the present article serves as the proceedings of the Conference with summaries of the presentations.